Formation of Nε-Carboxymethyl-Lysine and Nε-Carboxyethyl-Lysine in Pacific Oyster (Crassostrea gigas) Induced by Thermal Processing Methods - Zhou, Pengcheng; Dong, Shiyuan; Zeng, Mingyong (Frontiers in Nutrition, 2022)
Advanced glycation end products (AGEs) are important endogenous hazardous substances produced during the thermal processing of foods, which have attracted much attention due to the potential health risks. The current research first investigated the effect of different thermal processing methods (steaming, boiling, sous vide (SV), and sterilizing) on the formation of two typical markers of AGEs, including Nε-carboxymethyl-lysine (CML) and Nε-carboxyethyl-lysine (CEL), in Pacific oyster (Crassostrea gigas). The compositions, lipid oxidation, di-carbonyl compounds, and AGEs in 12 kinds of processed oysters were detected, and the Index values (total Z-score) were calculated. The SV treatment at 70°C caused higher processing yield and lower CEL level while sterilizing in oil at 121°C greatly resulted in the formation of CML. The Index value of SV-treated oysters was much lower than steamed, boiled, and sterilized ones. Correlation analysis showed that the CML and CEL levels were positively correlated with fat content, a* and b* value (p < 0.05), and negatively correlated with moisture content and L* value (p < 0.05). Besides, thiobarbituric acid reactive substances had a negative correlation with CML (r = -0.63, p < 0.05) while no significant correlation with CEL (p > 0.05), suggesting that lipid oxidation had a greater effect on the formation of CML but less on the formation of CEL. In summary, SV treatment at 70°C within 15 min was a recommended thermal processing method to reduce the formation of AGEs in oysters